2008
DOI: 10.1111/j.1439-0396.2007.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cumulus cells on rabbit oocyte in vitro maturation

Abstract: Cumulus cells (CCs) are of great importance in oocyte development and maturation in many species, but detailed influence of CCs has not been extensively examined, especially on rabbit. The present study was designed to investigate the effects of CCs and the elongation of in vitro maturation (IVM) time on rabbit oocyte nuclear and ooplasmic maturation and survival. Cumulus oocyte complexes (COCs) and naked oocytes (NOs) were recovered directly from rabbits super-ovulated with eCG. Corona-enclosed oocytes (COs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Cumulus cells are of critical importance for the final stages of oocyte nuclear and cytoplasmic maturation (Goud et al 1998, Moor et al 1998, because compounds such as amino acids and pyruvate enter the oocytes through the cumulus cell foot processes (Gilchrist et al 2004). With the decrease in the layers of cumulus cells surrounding rabbit oocytes, the maturation rates declined (Tao et al 2008). The presence of cumulus cells and corona cells also significantly improves the developmental potential of matured oocytes post-fertilization (Anderiesz & Trounson 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulus cells are of critical importance for the final stages of oocyte nuclear and cytoplasmic maturation (Goud et al 1998, Moor et al 1998, because compounds such as amino acids and pyruvate enter the oocytes through the cumulus cell foot processes (Gilchrist et al 2004). With the decrease in the layers of cumulus cells surrounding rabbit oocytes, the maturation rates declined (Tao et al 2008). The presence of cumulus cells and corona cells also significantly improves the developmental potential of matured oocytes post-fertilization (Anderiesz & Trounson 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Removal of cumulus cells before in vitro maturation (IVM) procedures reduces the developmental potential of oocytes of many species, including mouse (Anderiesz & Trounson 1995, Chang et al 2005, rabbit (Tao et al 2008), pig (Wongsrikeao et al 2005), cow (Chian et al 1994), and human (Johnson et al 2008). Cumulus cells are of critical importance for the final stages of oocyte nuclear and cytoplasmic maturation (Goud et al 1998, Moor et al 1998, because compounds such as amino acids and pyruvate enter the oocytes through the cumulus cell foot processes (Gilchrist et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based upon our observations that the nuclear maturation rates did not show significant difference between CCs denuded group and intact group, we suggest that this effect may be mediated by improved cytoplasmic maturation [42]. It has been shown that the cumulus cells are very important to complete oocyte cytoplasmic maturation in mouse, sheep, rats, cattle and pigs [11,36,37,40,43]. Many oocytes are mature in nucleus but immature in ooplasm after IVM.…”
Section: Discussionmentioning
confidence: 61%
“…Many oocytes are mature in nucleus but immature in ooplasm after IVM. As a consequence, this asynchronization could compromise on the developmental potential [37]. It has been demonstrated that cumulus cells co-culture starting at various IVF stages has no effect on fertilization and cleavage development but significantly improves rates of embryo development to morula or blastocyst stages [44].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation